Metaphors and Legal Language: a Few Comments on Ordinary, Specialised and Legal Meaning - Wojtczak, Sylwia; Witczak-Plisiecka, Iwona (Research in Language, 2019)
The present text offers a few comments on the metaphorical dimension of legal language and the nature of legal language as such. The authors discuss selected metaphors in the context of the Polish legislation with the aim to show how the metaphorical dimension of language can be used and abused. It is also demonstrated that the metaphorical dimension of language can cross-cut the interface between language and law on different levels. There are metaphors in legal texts that can be deliberately used to emphasise or cover selected aspects of meaning, and others that can just happen to act irrespective of any premeditated action on the part of the legislator. Finally, in a wider perspective, it is shown that the relation between ordinary language and the language of the law, i.e. ordinary meaning and legal meaning, may itself be seen as a relation between two domains within which metaphorical mapping takes place. It is claimed that the divide between the realm of law and the “real world” goes beyond a trivial division relative to expertise in the law and expertise in legal discourse, but can be better understood as the division between the legal community and the non-legal community including the academia where linguists reside.